An efficient approach for solving a class of nonlinear 2D parabolic PDEs - Dongjin Kim; Wlodek Proskurowski (International Journal of Mathematics and Mathematical Sciences)
We consider a class of nonlinear 2D parabolic equations that allow for an efficient application of an operator splitting technique and a suitable linearization of the discretized problem. We apply our scheme to study the finite extinction phenomenon for the porous-medium equation with strong absorption. A comparison of accuracy and computational efficiency of the resulting algorithms for several test problems is presented.